Acral Coactivation Therapy method in terms of improving the musculoskeletal system in pupils in physical and sport education - Bendíková, Elena; Balkó, Iva (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The quality of the musculoskeletal system in children is important in terms of primary prevention of postural health in adulthood. Aim of Study. The pilot study focused on the implementation of the Acral Coactivation Therapy (ACT) method in the teaching of physical and sport education in terms of improving the postural health of pupils with an emphasis on the muscular system and overall posture as a manifestation of its functionality. Material and Methods. The sample consisted of n = 16 pupils (14.21 ± 0.71 years; 54.25 ± 4.25 kg; 161.09 ± 4.56 cm) attending primary school. In terms of ensuring longevity and cross-sectionality in the surveys, available and standardized methods for physical education practice were applied. Results. The obtained results point to the followeing findings. While in control period V (1-2) we did not notice significant changes (p > 0.05) in the area of body posture and muscular system, in experimental period V (3-4), after applying the ACT method, we noticed overall significant (Wtest p < 0.05, r = 0.69) changes in the overall body posture of pupils with a high effect size, as well as in the muscular system (p < 0.05). In terms of difference and comparison of changes between control V (1-2) and experimental V (3-4) period ES (n = 16) in body posture and muscle groups, we noticed significant differences in favor of experimental period V (3-4), (Mann–Whitney test p < 0.05). Conclusions. These findings point to the importance of the application of targeted exercises in relation to the pupil’s postural health, implemented in physical and sport education. At the same time, there is a significant need to improve the content of the subject physical education and sport in terms of diversification and towards the health of pupils.
Keywords: ACT method; physical education and sport; musculoskeletal system; pupils